Peripheral Interface Controller (PIC) Based Maximum Power Point Tracking (MPPT) Algorithm For Photovoltaic (PV) DC To DC Boost Converter - Siam, Effendy Onn (UTeM, 2016)
This report is about to develop of Maximum Power Point Tracking (MPPT) algorithma for photovoltaic (PV) by using Peripheral Interface Controller (PIC). PV Module is a photovoltaic system that uses the photovoltaic array as a source of electrical power supply. Every photovoltaic (PV) array has an optimum operating point, called the maximum power point, which varies depending on PV temperature, the insolation level and array voltage. The function of MPPT is needed to operate the PV array at its maximum power point. The design of a MPPT is proposed utilizing a boost-converter topology. Solar panel voltage and current are continuously monitored by a closed-loop microprocessor based control system, and the duty cycle of the boost converter continuously adjusted to extract maximum power. The design consists of a PV array, DC - DC Boost converters (also known as step-up converters) and a control section that uses the PIC18F4550 microcontroller. Thus, the output voltage from DC-DC boost converter will be boost up approximately to 60V DC output voltage from load and should minimize in ripple voltage and tends to reach constant DC output voltage. Therefore, the conversion of sustainable energy from Photovoltaic (PV) system and step up by DC-DC boost converter circuit will be capable utilize large amount of output voltage. The control section obtains the information from the PV array through microcontroller’s Analog to Digital Converter (ADC) ports and hence to perform the pulse width modulation (PWM) to the converter through its Digital to Analog Converter (DAC) ports. Many such algorithms have been proposed. However, one particular algorithm, the constant voltage method, claimed by many in the literature to be inferior to others, continues to be by far the most widely used method in commercial PV MPPT’s. The microcontroller is programmed with a simple and reliable MPPT technique.